Using blog to Promote English Skills for EFL Students: The Students’ Perception - Budianto Hamuddin (ELT-Lectura, 2016)
Blogs in many modern institutions have been used to promote English skills in ELT situation. Thisquantitatif study aimed to identify and describes the use of blog to promote English skills for EFL students inPBIG FKIP Unilak. This study based its data from 118 students who attended 4 different classes based-blog.Employing a total sampling technique, the students were invited to fill up online questionnaire. Thequantitative data shows the majority (98%) of the students had a positive perception that blog was very usefuland (97%) effective as a media to promote English language skills. This postive result means that blog can beused as a media of learning to promote English skills among EFL students based on the perception of studentswho have used blog in 4 different classes-based blog in PBIG FKIP Unilak.